(untitled) (Research, Society and Development, 2021)
Objective: This study aimed to relate the behavioral characteristics of patients with autism spectrum, aiming to discuss relevant perspectives on their psychological approach in the dental office. Methodology: The research used as databases: Scielo, google scholar, and Pubmed, in addition to having carried out an initial theoretical basis with searches in the national literature of journals, specialized books, and research that addressed themes inherent to Psychology, Psychiatry, and Oral Health. The following descriptors were used to compose the search strategy: “autism”; "dental care"; "management"; “Oral health”. Results: It was possible to analyze a lack in the literature to the psychological approach of the autistic person in the dental environment. The best methodologies of psychological approaches for the autistic patient were “tell-show-do”; positive reinforcement; elimination of stressful sensory stimuli; clear and objective orders and establishment of a service routine. Conclusions: Although attending the autistic public presents itself as a challenge, depending on the degree of mental behavior of the patient, dental treatment is feasible on an outpatient basis, as long as previous adaptation work is carried out.